2022
DOI: 10.1007/s12033-022-00567-0
|View full text |Cite
|
Sign up to set email alerts
|

A Review on the Mechanism and Applications of CRISPR/Cas9/Cas12/Cas13/Cas14 Proteins Utilized for Genome Engineering

Abstract: The clustered regularly interspaced short palindromic repeats (CRISPR) and CRISPR-associated protein (CRISPR/Cas) system has altered life science research offering enormous options in manipulating, detecting, imaging, and annotating specific DNA or RNA sequences of diverse organisms. This system incorporates fragments of foreign DNA (spacers) into CRISPR cassettes, which are further transcribed into the CRISPR arrays and then processed to make guide RNA (gRNA). The CRISPR arrays are genes that encode Cas prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(29 citation statements)
references
References 85 publications
2
27
0
Order By: Relevance
“…Secondly, Cas9 nuclease is applicable to a broad temperature range, whereas Cas12b nuclease has a higher temperature requirement; therefore, the optimal dissociation temperature for Cas12b nuclease is greater than 40 °C. When the reaction temperature was 37 °C, wild-type BhCas12b preferentially cut complementary DNA without forming double-strand breaks, resulting in a decrease in editing efficiency, which was hypothesized to be due to the difficulty of target DNA accessing the RuvC site of BhCas12b [ 56 ], as well as the difficulty of target DNA accessing the RuvC site of BhCas12b. By mutating BhCas12b, researchers increased the DNA’s affinity for the Cas mutant protein, thereby removing the reaction temperature restriction on the use of Cas12b in mammals [ 28 ].…”
Section: Mechanism Of Molecular Detection Technology Based On Crispr/...mentioning
confidence: 99%
“…Secondly, Cas9 nuclease is applicable to a broad temperature range, whereas Cas12b nuclease has a higher temperature requirement; therefore, the optimal dissociation temperature for Cas12b nuclease is greater than 40 °C. When the reaction temperature was 37 °C, wild-type BhCas12b preferentially cut complementary DNA without forming double-strand breaks, resulting in a decrease in editing efficiency, which was hypothesized to be due to the difficulty of target DNA accessing the RuvC site of BhCas12b [ 56 ], as well as the difficulty of target DNA accessing the RuvC site of BhCas12b. By mutating BhCas12b, researchers increased the DNA’s affinity for the Cas mutant protein, thereby removing the reaction temperature restriction on the use of Cas12b in mammals [ 28 ].…”
Section: Mechanism Of Molecular Detection Technology Based On Crispr/...mentioning
confidence: 99%
“…Since this test relates to the identification of the human genome, it is likely to be used to diagnose cancer at various stages, particularly in the initial steps of incubation. [161,187,188] Lu et al investigated a CRISPR-Cas12a-based fluorescence bioassay by coupling advanced technologies, including terminal deoxynucleotidyl transferase (TdT), magnetic nanoparticles (MNP), and strand displacement (SDR) to detect lung cancer-induced exosomal miR-21. They found that the CRISPR-Cas12a-based fluorescence bioassay against mismatched sequences had a high specificity as well as a high sensitivity of about 161 fM for the determination of miR-21.…”
Section: Crispr As a Tool For Diagnosismentioning
confidence: 99%
“…These tests are also completed swiftly. Since this test relates to the identification of the human genome, it is likely to be used to diagnose cancer at various stages, particularly in the initial steps of incubation [161,187,188] . Lu et al.…”
Section: Crispr‐cas 9 Systems: Components and Limitationsmentioning
confidence: 99%
“…22 Third, both Cas12 and Cas13 are widely exploited in POC tests because of their unique trans-cleave ability, but they have different cleavage preferences: Cas12 can recognize and hydrolyze target DNA, and the recognition usually requires a PAM sequence; on the contrary, Cas13 does not need a PAM sequence, but can only recognize and hydrolyze ssRNA. 23 Thus, Cas12 and Cas13 can be utilized to detect different kinds of targets. In addition, due to their different cleavage objects, Cas12 and Cas13 systems can also be combined within one system to orthogonally test dual targets.…”
mentioning
confidence: 99%